Art and Design Pedagogy for Tomorrow’s Lifelong Learners - Pun, Siu Kay (Advances in Social Sciences Research Journal, 2014)
Globalisation, the knowledge economy, and advances in technologies have changed the way we live and work. They demand a new generation of graduates who can adapt to the new and constantly changing environment and yet remain competitive. This paper argues that educators need to examine the traditional ways of teaching and of producing knowledge expertise. The urgent demand now is for knowledge inquirers and creators, and self-directed lifelong learners. Using case studies of two art and design general electives, this paper examines the pedagogical role of art and design in nurturing lifelong learning skills. Based on student responses to learning and teacher observations, the result is positive. The pedagogical approaches described in this study can serve as a model for general studies education to nurture lifelong learning skills and to raise the standard of design literacy in nondesign students.